2020
DOI: 10.1002/pd.5760
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to studying the genomic architecture of complex birth defects

Abstract: Every year nearly 6 percent of children worldwide are born with a serious congenital malformation, resulting in death or lifelong disability. In the United States, birth defects remain one of the leading causes of infant mortality. Among the common structural congenital defects are conditions known as neural tube defects (NTDs). These are a class of malformation of the brain and spinal cord where the neural tube fails to close during the neurulation. Although NTDs remain among the most pervasive and debilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
(138 reference statements)
0
6
0
Order By: Relevance
“…as there is already published evidence to suggest that SWV embryos may metabolize VPA differently. Genomic fine mapping of exencephalic fetuses derived from SWV/C57 backcrossing identified a 33 MB sensitivity locus which contains genes coding for members of the ACSM family of enzymes involved in VPA metabolism ( Taiwo et al, 2020 ). ACSM enzymes catalyze conversion of VPA to valproyl-coA, a critical first step required for further metabolism via mitochondrial β-oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…as there is already published evidence to suggest that SWV embryos may metabolize VPA differently. Genomic fine mapping of exencephalic fetuses derived from SWV/C57 backcrossing identified a 33 MB sensitivity locus which contains genes coding for members of the ACSM family of enzymes involved in VPA metabolism ( Taiwo et al, 2020 ). ACSM enzymes catalyze conversion of VPA to valproyl-coA, a critical first step required for further metabolism via mitochondrial β-oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made to discern underlying factors contributing to VPA susceptibility in the SWV strain, which is sometimes referred to as SWV-Fnn. Gene expression analysis revealed strain-dependent alterations in folate and one-carbon metabolism pathway genes ( Finnell et al, 1997 ), and genomic fine mapping has been reported on in several publications over the last 2 decades, where intercrossing the C57 and SWV-Fnn strains led to identification of a candidate sensitivity locus ( Beck, 1999 ; Finnell et al, 2000 ; Beck, 2001 ; Lundberg et al, 2004 ; Taiwo et al, 2020 ). Notably, the sensitivity locus contained all but one member of the acyl-CoA synthetase-medium chain (ACSM) family of genes, the exception being the gene encoding ACSM4.…”
Section: Introductionmentioning
confidence: 99%
“…We determined that recombination events had occurred in the chromosomal region located between D7Mit285 and D7Mit101 , which cover a 3.3-Mb region. This helped to establish the presence of a chromosomal region that contained a major gene or genes that regulates susceptibility to VPA-induced NTDs in mice ( Figure 1 ; Taiwo et al, 2020 ). More robust genomic tools can now be applied to further refine this region of interest and better define those genetic factors regulating sensitivity to VPA’s teratogenicity in mice.…”
Section: Discussionmentioning
confidence: 99%
“…7 Their polygenic nature necessitates the use of genomics-based approaches to elucidate the genetic layout underlying them. With the advent of whole-genome sequencing, 8 whole-exome sequencing, 9 and next-generation sequencing (NGS), 10 the cumulative number of genes associated with NTDs has increased. 11 Most of the known candidate genes associated with NTDs are closely associated with the folate metabolic pathway 12 and several developmental signaling processes pivotal for neural tube closure, such as WNT-including the canonical β-catenin/WNT 13 and noncanonical WNT/planar cell polarity (PCP) 14 pathways-and the sonic hedgehog signaling 15 pathways.…”
Section: Introductionmentioning
confidence: 99%